Influências de práticas de colaboração da inovação aberta no desempenho operacional, de mercado e inovador - Scaliza, Janaina Aparecida Alves [UNESP] (2015)
The objective of this research is to analyze the relationships of influence between collaborative practices proposed by the Open Innovation approach, with aspects of organizational culture and organizational structure. In addition, we intend to analyze the influences of collaboration for innovations with operational performance, innovative performance and market performance. A quantitative survey was adopted, with a sample of 116 firms in sectors considered dynamics in terms of technology. Some of the results presented that customers are the main source of collaboration for innovation companies; those companies that receive govermnment incentives for innovation are less prone to the use of collaborative innovation practices; there is a preponderance of large companies in the development of radical innovations; collaborative relations proposed by Open Innovation approach with customers, suppliers, employees, universities and others, exert positive influences both innovative performance as the market firms, but has no positive influence on operating performance